The Effects of Camelina “Soheil” as a Novel Biodiesel Fuel on the Performance and Emission Characteristics of Diesel Engine - Seyed Salar Hoseini; Gholamhassam Najafi; Barat Ghobadian; Talal Yusaf; Mohammad Taghi Ebadi (Applied Sciences, 2018)
In this research, a new cultivar of Camelina “Soheil” seed oil (CSO) was investigated as a novel feedstock for biodiesel production. Maximum oil content of CSO seed was about 29%. Physical and chemical characteristics of CSO were investigated. The biodiesel production process was optimized by using the response surface methodology (RSM) reaction parameters, including molar ratio (methanol to oil), reaction time, and concentration of catalyst are studied. The result showed that the conversion of biodiesel was 98.91% under the optimized conditions of 10.18:1 molar ratio and 1.15 wt % concentration of catalyst for a reaction time of 7.33 min. By investigating the properties of the fuel, it turned out that biodiesel from new cultivar of CSO oil complied with the limits prescribed in the ASTM D6751 standards, and that this seed oil could be introduced as a new feedstock for biodiesel production. Also, the performance and emission of a diesel engine were investigated with CSO biodiesel. All of the engine experiments were performed under the constant speed of 2100 rpm at loads of 0%, 25%, 50%, 75%, and 100%. Results indicated that by using the biodiesel-diesel blends, the brake power, and the CO2 and NOx emissions increased, while the SFC and CO and UHC emissions decreased.